Epigenetic changes induced in mice liver by methionine-supplemented and methionine-deficient diets. (May 2022) - Aissa, Alexandre Ferro; Tryndyak, Volodymyr P.; de Conti, Aline; Rita Thomazela Machado, Ana; Tuttis, Katiuska; da Silva Machado, Carla; Hernandes, Lívia Cristina; Wellington da Silva Santos, Patrick; Mara Serpeloni, Juliana; P Pogribny, Igor; Antunes, Lusânia Maria Greggi
Abstract: A diet deficient in donors of methyl group, such as methionine, affects DNA methylation and hepatic lipid metabolism. Methionine also affects other epigenetic mechanisms, such as microRNAs. We investigated the effects of methionine-supplemented or methionine-deficient diets on the expression of chromatin-modifying genes, global DNA methylation, the expression and methylation of genes related to lipid metabolism, and the expression of microRNAs in mouse liver. Female Swiss albino mice were fed a control diet (0.3% methionine), a methionine-supplemented diet (2% methionine), and a methionine-deficient diet (0% methionine) for 10 weeks. The genes most affected by the methionine-supplemented diet were associated with histone and DNA methyltransferases activity, while the methionine-deficient diet mostly altered the expression of histone methyltransferases genes. Both diets altered the global DNA methylation and the expression and gene-specific methylation of the lipid metabolism gene Apoa5 . Both diets altered the expression of several liver homeostasis-related microRNAs, including miR-190b-5p, miR-130b-3p, miR-376c-3p, miR-411–5p, miR-29c-3p, miR-295–3p, and miR-467d-5p, with the methionine-deficient diet causing a more substantial effect. The effects of improper amounts of methionine in the diet on liver pathologies may involve a cooperative action of chromatin-modifying genes, which results in an aberrant pattern of global and gene-specific methylation, and microRNAs responsible for liver homeostasis. Highlights: Methionine-supplemented diet altered the expression of chromatin-modifying genes. Similar gene expression changes were induced also by methionine-deficient diet. Histone methyltransferases were the most up-regulated genes with both diets. Both diets increased global DNA methylation in mouse liver. Both diets altered the expression of several liver homeostasis-related microRNAs.